Response of cowpea and soybean to P and K on terre de barre soils in southern Benin - Carsky, R.J. (Elsevier, 2003)
Good growth of Grain Legumes helps food security and protection of the environment but this may require nutrient inputs. A participatory technology development activity explored from 1998 to 2000 the responses of cowpea (Vigna unguiculata) and soybean (Glycine max (L.) Merr.) to inorganic soil amendments (P and K) on terre de barre soils with different levels of degradation in southern Bénin. Adingnigon, on the Abomey plateau, represents a level of severe degradation, while Hayakpa, on the Allada plateau, is still relatively non-degraded. Treatments included: (i) an unamended control, (ii) P fertilizer only, applied in 1998 or 1999, and (iii) P plus K applied in 1999. At Hayakpa, yields without fertilizer were generally moderate to high; responses to P were statistically significant and K application had a significant effect on soybean yield in 2000. At Adingnigon, P application had a large relative effect (30–200%) but a small absolute effect (less than 100 kg/ha) on cowpea and soybean yield. Subsequent K application increased grain yields further (approximately 100 kg/ha) but still not up to the cowpea yield potential. When 13 Mg/ha of organic amendment (chicken manure or cotton seed) were applied to severely degraded plots at Adingnigon with prior grain yields below 200 kg/ha, cowpea yields of more than 500 kg/ha were achieved, approaching their biological potential for the zone. It is clear from this study that (i) P and K inputs are needed for Grain Legumes even on relatively non-degraded terre de barre soils and (ii) inorganic fertilizer alone will not revive highly degraded soils on the terre de barre plateaus of southern Bénin.